Tidal Modulation of Hydrothermal Tremor: Examples From Ischia and Campi Flegrei Volcanoes, Italy - Petrosino, Simona; Dumont, Stéphanie (Frontiers in Earth Science, 2022)
In the present study, we investigate the tidal influence on two volcanoes, Ischia and Campi Flegrei (Southern Italy), charachterized by intense hydrothermal activity. We analyse seismic tremor of hydrothermal origin recorded by four seismic stations between January and June 2020 by using Singular Spectrum Analysis. We detect up to 5 medium/long term tidal periodicities ranging from 5 to 29 days. The results indicate that the seismic tremor is modulated by Earth tides at both volcanoes. In addition, differences in phase and amplitude modulation between the response of hydrothermal systems of Ischia and Campi Flegrei to tidal forcing, reveal specific features related to the tremor source and the properties of the underlying rocks. The observed phenomena indicate a close interplay between solid Earth and the dynamics of these two volcanic systems.